Pengaruh Faktor Produksi Terhadap Pendapatan Petani Padi Di Desa Terjun Kecamatan Pantai Cermin Kabupaten Serdang Bedagai - Puspa Sari; Adriansyah Yoesoef; Siska Yulianita Lubis (Universitas 17 Agustus 1945 Semarang, 2023)
The Influence of Production Factors on the Income of Rice Farmers in the Waterfall Village, Pantai Cermin District, Serdang Bedagai Regency. This study uses 1 dependent variable and 3 independent variables. The dependent variable is rice farming income, while the independent variables are capital, land area and labor. While the object of research is the farmers of the Village of Waterfall, Pantai Cermin District, Serdang Bedagai Regency. Linear regression explains the contribution of the independent variable to the dependent variable so that it can be concluded that this variable has a positive effect on the income of rice farmers. In other words, if the studied variable increases, it will be followed by an increase in rice farming income. Simultaneously (together) the variables studied have a real influence on rice farming income and of the 3 variables studied, partially there is 1 variable, namely the variable land area which has a significant effect on income while 2 variables, namely capital and labor variables have no effect the real impact on the income of rice farmers in the village of Waterfall, Pantai Cermin District.